Innovational Communication Strategy for Sustainable Farming Fisheries Development Bogor District - Riyantini, Rini; Muljono, Pudji; Diatin, Iis; Gondasari, Dyah (Future Science / FSH-PH Publications, 2023)
Identify the frequency, direction, content, communication channels, characteristics and stages of adoption of innovations for cultivators and development of sustainable aquaculture in Bogor Regency and analyze the effect of frequency, direction, content, communication channels on the stages of adoption of innovations for catfish enlargement cultivators in Bogor Regency. This study uses a pragmatic paradigm with a mixed approach or method because the innovation communication strategy for the development of sustainable aquaculture is not enough to answer only by measuring the influence between variables in a post-positivist manner, but needs to be traced through the process of communication of innovation between cultivators as actors. Data collected based on data sources consist of primary data and secondary data. Primary data is data obtained directly from respondents at the time the research was conducted, while secondary data is supporting data that is already available at the research location obtained from the Livestock and Fisheries Service of Bogor Regency, data available to extension workers and data available to extension workers. catfish rearing group. Research Results Based on the test results related to whether or not the influence of the independent variable on the dependent variable can be seen based on t count and significant value. From the table above, the ttable value is 13.843 > 2.042 (ttable obtained by finding df and looking at ttable, df = number of correspondents - 2 and a significance value of 0.00 <0.05. Based on these measurements, the R value is obtained at 0.930, and after interpretation it is known that there is a very high relationship between the variables x and y.The R Square test (R2) is used to determine how much influence the value of the regression coefficient (R) states there is a correlation between the independent and dependent variables.